Editorial for the Special Issue on Implantable Microdevices - Wen Li; Zhen Qiu (Micromachines, 2019)
Implantable microdevices, providing accurate measurement of target analytes in animals and humans, have always been important in biological science, medical diagnostics, clinical therapy, and personal healthcare [...]